Algae as a renewable energy Source: Potential and feasibility - Imran Hasan (Peerian Journals Publishing, 2021)
Algae as a biodiesel is on the verge of being the best alternative for oil although algae are said to be economically viable at the end of 2040, so the algae biodiesel is the future of green technologies. This paper emphasizes on the usage of algae biodiesel the production rate, the amount of biodiesel produced from the per acre crops. The process of extracting biodiesel from algae. The economic viability of algae biodiesel the different products of algae biodiesel the economic viability of algae biodiesel. The advantages of algae and the future usage of algae biodiesel. Also, this paper discusses the possible impact of algae biodiesel on economy.
Keywords: Algae; Biofuel; Economy; Alternative Energy